Kajian Stabilitas Konstruksi Culvert Bridge dalam Mitigasi Debit Banjir Kala Ulang 50 Tahun di Kawasan Industri Gas Kabupaten Barito Utara - Saputra, Cahyo Agung; Maini, Miskar (Universitas Sarjanawiyata Tamansiswa, 2025)
Culvert bridges are an important part of industrial drainage systems that must be evaluated for stability. Construction stability is a crucial factor, especially in the gas industrial area of ​​North Barito Regency, which has an extreme risk of flooding. This research uses hydraulic and geotechnical analysis to evaluate the safety factors of culvert bridges from the hydraulic and construction stability aspects. The research results show that to flow the design discharge with a return period of 50 years (Q50) of 13.78 m³/s, a culvert with a diameter of 2.967 m is required. With the addition of 25% freeboard, the design diameter increases to 3.709 m. However, the materials available are two steel pipe units with a diameter of 3 m. Hydraulic calculations show that one culvert with a diameter of 3 m can carry a discharge of up to 15,047 m³/s, so two culvert units can accommodate 30,093 m³/s, far exceeding the design discharge. Meanwhile, the stability analysis results show a safety factor (SF) against overturning 5.98 and against sliding 4.473, both exceeding the recommended safe limits. Apart from that, the bearing capacity of the subgrade is also sufficient, with a maximum stress of 528.475 kN/m², still far below the allowable stress of 868.8582 kN/m². The results of this research confirm that the two culvert designs not only meet the hydraulic and geotechnical criteria. However, they can also effectively channel the designed flood discharge with a high level of safety.